French of the present and the past: the representation of the Parisian vernacular in Maurice Chevalier's songs - Abecassis, Michaël (Linguistik Online, 2005)
Today in France, there seems to be a resurgence of interest in 1930s French culture, with the release of Le Fabuleux destin d'Amélie Poulain (2001), set in Montmartre, and Patrick Bruel's re-edition of 1930s popular songs (2002). Songs of the 1930s and 1940s have hardly been exploited by linguists. I have compiled a corpus of Maurice Chevalier's songs whose lexical items I have analysed to assess how language has evolved. The stereotypical representation of the lower class which was a popular theme in musical-hall songs at that time enables the analysis of vernacular forms used at the beginning of the 20th century. I willendeavour in this analysis to establish the change in attitudes towardsthe standard and stigmatised language varieties in France by looking at lexicographers' labelling of non-standard items with stylistic indicators such as familier, populaire and argotique. I also intend to gauge through a survey conducted recently in France whether the once denigrated français populaire found in Chevalier's songs is obsolete or whether it is still used in the 21st century. Keywords: songs, French, français populaire, Maurice Chevalier, non-standard, lexis